The Role of Social Media as an Alternative Learning Resource Among University Students - Muh. Ibnu sholeh (Journal of Educational Research and Practice, 2025)
This research is motivated by the increasing use of social media among students of STAI KH. Muhammad Ali Shodiq, which has not yet been fully optimized as a learning resource. Although social media holds great potential in supporting digital learning, several problems persist, such as low levels of digital literacy, a lack of lecturer guidance in academic use of social media, and a tendency among students to focus more on entertainment rather than educational content. This study aims to analyze students’ patterns of social media use, the types and forms of educational content utilized, as well as the supporting and inhibiting factors within the context of modern Islamic learning. The research employs a qualitative descriptive method with data collection techniques including observation, in-depth interviews, and documentation involving active students from various study programs. The findings reveal that social media platforms such as YouTube, Instagram, and WhatsApp have become effective alternative learning sources, particularly in enhancing students’ understanding of Islamic materials and academic communication. Students have also begun to act as producers of simple educational content, although they still face challenges in information curation and maintaining digital learning discipline. The implications of this study emphasize the importance of the role of lecturers and institutions in integrating social media into Islamic value-based learning strategies to foster a reflective, creative, and digitally literate learning culture.